IDENTIFIKASI PATAHAN DI DESA TAMAN AYU KECAMATAN GERUNG KABUPATEN LOMBOK BARAT MENGGUNAKAN METODE GEOMAGNET - Deni Hermansyah; Bakti Sukrisna; Suhayat Minardi (Jurnal Geofisika Eksplorasi, 2020)
This research aimed to identify the presence of faults in Taman Ayu Village, Gerung District, West Lombok Regency by mapping the magnetic field. The fault outcrops found near this location becomes the reason to suspected the fault existence that reaching residents, farming area and access roads, so it is necessary to study the type, depth and direction of the fault. Measurements were made on 11 lines with a length of each line is 3 km. Each line of measurement is 300 m apart from each other and the distance between measurement points is 50 m, 100 m, and 200 m depending on the distance from the target location. Separation between regional anomalies and residual anomalies using the upward continuation method at an altitude of 1000 m. Qualitative interpretation of residual anomalies results in low anomalies with values from -890.9 nT to 897.3 nT. Quantitative interpretation of the five cross sections by the inverse modeling method with Oasis Montaj 6.4.2 software resulting subsurface geological structures in the form of normal fault. This normal fault is at a depth of 30 m to 480 m which is composed of layers of silt, sandy silt, sand, clay and breccia. The fault passes through Gapuk Village, Taman Ayu and Kebon Ayu and passes through the highway in Northeast – Southwest direction